Steelheart - Sanderson, Brandon (New York : Ember, 2014)
At age eight, David watched as his father was killed by an Epic, a human with superhuman powers, and now, ten years later, he joins the Reckoners--the only people who are trying to kill the Epics and end their tyranny.
Includes excerpts from Firefight, the Reckoners, book two.
HL 680
Accelerated Reader AR
Keywords: Supervillains -- Fiction; Guerrilla warfare -- Fiction; Young adult fiction; Science fiction